Central pulse pressure is inversely associated with proximal aortic remodelling. Issue 5 (May 2021) - Tosello, Francesco; Guala, Andrea; D'ascenzo, Fabrizio; Bollati, Martina; Leone, Dario; Sabia, Luca; Bruno, Giulia; Mingrone, Giulia; Astarita, Anna; Vallelonga, Fabrizio; Avenatti, Eleonora; Moretti, Claudio; et al.
Abstract : Objectives: Hypertension leads to aortic stiffening and dilatation but unexpected data from the Framingham Heart Study showed an inverse relationship between brachial pulse pressure and aortic diameter. Aortic dilatation would not only lead to lower pulse pressure but also to a worse prognosis (cardiac events, heart failure). Invasive pressure may be more informative but data are lacking. Aim: This study evaluated the relationship between invasively measured central blood pressure and proximal aortic diameter. Methods: In 71 consecutive patients referred to invasive haemodynamic study, proximal aortic remodelling was evaluated in terms of Z -score, comparing diameters measured at the sinus of Valsalva to the diameter expected according to patients' age, sex and body height. Pressures were recorded directly in the proximal aorta by means of a catheter before coronary assessment. Results: The mean invasive aortic SBPs and DBPs were 146 ± 23 and 78 ± 13 mmHg, respectively, giving a central pulse pressure (cPP inv) of 68 ± 21 mmHg. Proximal aortic diameter was 34.9 ± 19.4 mm, whereas Z -score was −0.3 ± 1.7. Patients with higher cPPinv showed a significantly lower Z -score (−0.789 vs. 0.155, P = 0.001). cPPinv was inversely related to Z -score ( R = −0.271, P = 0.022) independently from age, mean blood pressure and heart rate ( β = -0.241, P = 0.011). Conclusion: Aortic root Z -score is inversely associated with invasively measured central pulse pressure in a cohort of patients undergoing invasive coronary assessment. Remodelling at the sinuses of Valsalva may be a compensatory mechanism to limit pulse pressure. Abstract : Supplemental Digital Content is available in the text